2018
DOI: 10.1002/adma.201707312
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Polaron Formation and Charge Carrier Cooling in Lead‐Iodide Perovskites

Abstract: Notwithstanding the success of lead-halide perovskites in emerging solar energy conversion technologies, many of the fundamental photophysical phenomena in this material remain debated. Here, the initial steps following photogeneration of free charge carriers in lead-iodide perovskites are studied, and timescales of charge carrier cooling and polaron formation, as a function of temperature and charge carrier excess energy, are quantified. It is found, using terahertz time-domain spectroscopy (THz-TDS), that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

37
187
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(243 citation statements)
references
References 80 publications
37
187
5
1
Order By: Relevance
“…Note that the ω LO coherence and dephasing times, revealed in the time domain here by single-cycle intense THz pump, is close to the previous optical pump results that reveal the polaron mode ∼3.7 THz temporal oscillation [20] by detecting the differential frequency between weak THz probe and polaron collective emission. Note that all these results are consistent with the formation time ∼1ps of large polarons [27]. Polarization dephasing can lead to conversion of LO phonon coherence into population of polarons associated with the establishment of dynamic screening of Coulomb interactions.…”
supporting
confidence: 85%
“…Note that the ω LO coherence and dephasing times, revealed in the time domain here by single-cycle intense THz pump, is close to the previous optical pump results that reveal the polaron mode ∼3.7 THz temporal oscillation [20] by detecting the differential frequency between weak THz probe and polaron collective emission. Note that all these results are consistent with the formation time ∼1ps of large polarons [27]. Polarization dephasing can lead to conversion of LO phonon coherence into population of polarons associated with the establishment of dynamic screening of Coulomb interactions.…”
supporting
confidence: 85%
“…13 Second, the polaron formation stabilizes the hole and contributes to disfavoring the neutral interstitial. It has previously been shown that the electron, which could be trapped by I + i , also forms a polaron on a sub-picosecond timescale 28,29 and should lead to a similar behavior as the one described here for the hole. Third, the probability of hole trapping is reduced due to the efficient static screening of charges in CH 3 NH 3 PbI 3 , which will also hold for the electron and the I + i defect.…”
supporting
confidence: 69%
“…We use the experimental lattice parameters of the tetragonal phase of CH 3 NH 3 PbI 3 . 24 It has been indicated, both in experimental [25][26][27][28] and computational 27,29 studies, that free charges in CH 3 NH 3 PbI 3 form localized polaronic states. Therefore, to properly account for such states, the simulations are carried out with the hybrid functional PBE0.…”
mentioning
confidence: 99%
“…were able to observe the charge carrier cooling and polaron formation in various HaPs (Figure (a)) . On the other hand, the signal of time‐resolved optical Kerr effect (TR‐OKE) spectroscopy measurement on MAPbBr 3 single crystals was assigned to the variation of the Pb−Br−Pb angles in in a timescale <1 ps by Miyata et al (Figure 5 (b)) . By comparing the results from MAPbBr 3 and CsPbBr 3 , they concluded that polaron formation in the bromide system is predominately impacted by the tilting of the PbBr 6 3− octahedra.…”
Section: Polaron Formalism and Its Application In Hapsmentioning
confidence: 94%
“…[31] On the other hand, the signal of time-resolved optical Kerr effect (TR-OKE) spectroscopy measurement on MAPbBr 3 single crystals was assigned to the variation of the PbÀ BrÀ Pb angles in in a timescale < 1 ps by Miyata et al ( Figure 5 (b)). [32] By comparing the results from MAPbBr 3 and CsPbBr 3 , they concluded that polaron formation in the bromide system is predominately impacted by the tilting of the PbBr 6 3À octahedra. While these studies cannot be taken as conclusive proof of polarondominated charge transport in HaPs, they provide valuable information for future investigations.…”
Section: Polaron Formalism and Its Application In Hapsmentioning
confidence: 99%